CCR2 deficiency does not provide sustained improvement of muscular dystrophy in mdx5cv mice. Issue 1 (21st September 2016) - Zhao, Wanming; Wang, Xingyu; Ransohoff, Richard M.; Zhou, Lan
Abstract : Genetic ablation or pharmacologic inhibition of CC chemokine receptor type 2 (CCR2) reduced macrophage (MP) infiltration and improvedmuscle pathology and function in mdx diaphragmmuscle at early stages. We addressed whether CCR2 deficiency resulted in sustained improvement of mdx 5cv ‐ Ccr 2 2/2 diaphragm. Compared to mdx 5cv controls, CCR2 deficiency in mdx5cv‐ Ccr 2 2/2 mice markedly reduced intramuscular Ly6C hi MPs at all stages, but it reduced Ly6C low MPs only at early stages (4 and 9 wk). CCR2 deficiency reduced quadriceps and diaphragm muscle damage and fibrosis at 14 wk but not at ± mo, and it improved diaphragm muscle regeneration and respiratory function at 14wk but not at 6 mo. IntramuscularMPs in mdx 5cv ‐ Ccr 2 −/− diaphragm expressed a low level of IL‐1β, IL‐6, and IFN‐γ genes, a similar level of TNF‐α, TGF‐β1, and platelet‐derived growth factor a genes, and a high level of IGF‐1 and osteopontin genes compared to mdx 5cv controls. Diaphragm fibroblasts at 14 wk showed a similar cell number with a similar level of collagen and profibrogenic growth factor gene expression in mdx 5cv ‐ Ccr 2 −/− and mdx 5cv mice. Diaphragm MPs from both mdx 5cv ‐ Ccr 2 −/− and mdx 5cv mice stimulated collagen gene expression by cocultured fibroblasts. The findings suggest that CCR2 deficiency does not provide a sustained benefit and that Ly6C low MPs may contribute to the progressive fibrosis and dysfunction of mdx 5cv diaphragm.—Zhao, W., Wang, X., Ransohoff, R. M., Zhou, L. CCR2 deficiency does not provide sustained improvement of muscular dystrophy in mdx 5cv mice. FASEB J. 31, 35–46 (2017) www.fasebj.org